Diversity and distribution of Collembola in Gelam forest, Bachok, Kelantan - Nor Rashidah Asa’ari (2018)
The tittle of this study was the diversity and distribution of the Collembola in Gelam Forests, Bachok Kelantan. The purpose of this study were to determine the diversity and distribution of springtails (Insecta:Collembola) in Gelam Forests. These study were investigated in a Gelam forests using composite systematic sampling. The method used to sort out Collembola from core soil was Berlese Tullgren Funnels. A total of 235 individuals of Collembola from 9 families and ll genera were recorded. Overall, Family Brachytomellidae was the highest number of individuals has been collected and the most abundant family while the lowest number of individuals was family Tomoceridae and Entomobryidae. Families Hypogastruridae and Isotomidae were recorded with 2 genera of collembola. Hypogastrura and Ceratophysella for Hypogastruridae and lsotomiella and Anurophorus for Isotomidae.